Man as Object. The Denial of Dignity - Brugiatelli, Vereno (European Journal of Multidisciplinary Studies, 2020)
Considering and treating people as things, objects or instruments is easier than one may think. Marx and Lukacs have highlighted the fact that the different processes of reification (reducing man to an object) is rooted in market logic: philosophers of the Frankfurt School like Horkheimer, Marcuse and Adorno have identified their origin in the techno-scientific reasoning of capitalist society. In this paper I intend to demonstrate that their explanations embrace the phenomenon of reification in an incomplete way. Through Axel Honneth’s social philosophy I intend to show that the reduction of man to an object depends on the misrecognition of the qualities and dignity of man. Such misrecognition does not depend on market logic or techno-scientific reason, but rather on a certain attitude that man adopts towards himself and others.
Keywords: Man as Object, Reification, Capitalist society, Market, Misrecognition.